Pilot introduction of long-lasting insecticidal nets and hammock nets in the indigenous Comarca of Guna Yala, Panama - A. Oscar E. González; Carmen Perez; Tania Blanco; Cipriano Ayarza; Santiago Chérigo; Mario Ávila; Lucía Fernández Montoya; Nicholas A. Presley; Bernardo García Espinosa; Mariela Mosquera Renteria (Malaria Journal)
Abstract Background After almost 70 years of using indoor residual spraying (IRS) as the primary intervention for malaria vector control, the Republic of Panama wanted to evaluate the operational feasibility and acceptability of distributing long-lasting insecticidal hammock nets (LLIHNs) and long-lasting insecticidal nets (LLINs) in the country. Methods A pilot study conducted in 2019 distributed LLINs and LLIHNs to cover all sleeping spaces in 15 high burden localities of the indigenous Comarca of Guna Yala and measured retention, coverage, use and physical deterioration, washing and drying practices, as well as people’s satisfaction with product characteristics post-distribution. Results Overall, 89.9% of enumerated sleeping spaces were covered during the campaign. Monitoring post-distribution showed that 82.7% of the population received messages about the campaign before it happened and 92.4% claimed to know the purpose of the net and how to care for and repair it. Mild adverse reactions, specifically skin irritation associated with the insecticide in LLINs and LLIHNs, were reported by 38.4% of households. Two years after distribution, 86.3% of the LLIHN/LLINs were retained. Use was very high right after distribution (85%) but decreased to 57% six months after distribution and to 38% two years after distribution. The main reason for not using the LLIHN/LLINs was the reported absence of mosquitoes. Two years post-distribution, LLIHN/LLINs were preserved in good physical condition (4% torn), very few were washed with insecticide-damaging products (chlorine or detergent) (9%) or dried under the sun (15%), and LLIHN/LLINs were washed on average less than once every two months. The average number of people per sleeping space was 1.34. Conclusion Although the distribution of LLIHN/LLINs was operationally feasible and LLIHN/LLINs were initially well-accepted and cared for by these communities, use decreased drastically over the two years of follow up after distribution. Hence, should there be future LLIHN/LLIN distributions in this area, sufficient resources and efforts need to be allocated to promoting LLIHN/LLIN use. Further investigation into the reasons for low LLIHN/LLIN use are needed to guide such efforts.